Comparison of fatty acid profiles of sacha inchi oil (Plukenetia huayllabambana), sesame oil (Sesamum indicum), and peanut oil (Arachis hypogaea) using two extraction methods for food purposes - Plua Montiel, Jhoan; Neira Mosquera, Juan Alejandro; Sanchez Llaguno, Sungey Naynee; Aldas Morejon, Jhonnatan Placido; Revilla Escobar, Karol Yannela; Caicedo-Álvarez, Edgar (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Vegetable oil consumption has increased in recent decades due to the high content of monounsaturated (Omega 9) and polyunsaturated (Omega 3 and 6) fatty acids. For this reason, this research compared the fatty acid profile of sacha inchi, sesame and peanut oils under two extraction methods for food purposes. A completely randomized experimental design considered an A*B factorial arrangement with 3 repetitions. Factor A corresponds to oilseed type and Factor B is extraction method. The results showed that both factors significantly influenced (p<0.05) bromatological characteristics (pH, acidity, peroxide value, relative density and ash). The lowest concentration of saturated fatty acids was obtained in sacha inchi oil + cold pressing (6.80 g/100 g), while monounsaturated fatty acids increased in peanut oil + hot pressing (51.51 g/100 g). Sacha inchi oil + cold pressing had the highest content of polyunsaturated fatty acids (84.36 g/100 g). Highlights: Comparison of lipid profiles in sacha inchi, sesame, and peanut oils. Cold extraction preserves quality, hot extraction increases yield. Cold-pressed sacha inchi contains more polyunsaturated fatty acids. Hot-pressed peanut is more stable and has lower acidity. Sacha inchi provides omega-3, while peanut and sesame are more oxidation-stable.